A compositional turnover zone of biogeographical magnitude within lowland Amazonia - Tuomisto H; Moulatlet GM; Balslev H; Emilio T; Figueiredo FOG; Pedersen D; Ruokolainen K (WILEY-BLACKWELL, 2022)
Aim To assess the relative roles of geologically defined terrain types ( environmental heterogeneity) and a major river ( physical dispersal barrier) as predictors of ecological structuring and biogeographical differentiation within Amazonian forests.Location Western Brazilian Amazonia, where the Jurua river and its terraces cross a 1000-km-long boundary between two geological formations ( the Solimoes and Ica Formations).Methods We sampled a 500-km stretch of the Jurua with 71 transects ( 5 m by 500 m) that spanned both the river and the geological boundary. All transects were inventoried for pteridophytes ( ferns and lycophytes) and Melastomataceae, and a subset of 39 transects also for palms and Zingiberales. Three surface soil samples were collected from each transect. The data were analysed using ordinations, regression trees, indicator species analyses and Mantel tests.Results All plant groups showed congruent species turnover between geologically defined terrain types, but little evidence of isolation by the river or geographical distance. Soil cation concentration differed between the Solimoes Formation and other terrain types and emerged as the main explanatory factor for species turnover. A large proportion of the plant species were significant indicators for specific parts of the soil cation concentration gradient, and these edaphic associations were congruent with those found in other parts of Amazonia. Pteridophytes had a larger proportion of species in the cation-rich soils than the other plant groups did, and palms had a higher proportion of generalists.Main conclusions The geological boundary between the Solimoes and Ica formations is confirmed as significant floristic turnover zone. As it runs in a north-south orientation for more than 1000 km, the edaphic differences associated with this boundary have wide-ranging implications for speciation and biogeographical patterns in Amazonia.